Implementation of the Problem Based Learning Method to Enhance Students Learning Activities and Outcomes at SD Negeri 077786 Tuhembaruzo - Simatupang, Denar Yosafad; Fauzi, KMA (Pusdikra Publishing, 2025)
This study aims to improve students’ learning activities and outcomes through the implementation of the Problem-Based Learning (PBL) model in Grade IV students of SD Negeri 077786 Tuhembaruzo. The research subjects consisted of 18 students, including 8 boys and 10 girls. The study employed a Classroom Action Research (CAR) design using the Kemmis and McTaggart model, carried out in two cycles, each consisting of planning, action implementation, observation, and reflection. Data were collected through observations of learning activities, learning outcome tests, short interviews, and documentation, and were analyzed using both qualitative descriptive and quantitative approaches. The results show that the application of PBL significantly improved students’ learning activity. The average activity score increased from 53% in Cycle I to 83% in Cycle II, with notable improvement in problem reading, group discussion, questioning, expressing opinions, and presenting group work. Students’ learning outcomes also increased substantially. The average score rose from 58.3 in the pre-action stage to 71.1 in Cycle I, and further to 83.8 in Cycle II. Learning mastery improved from 22% to 50% in Cycle I, and reached 83% in Cycle II. These findings align with previous studies indicating that PBL is effective in enhancing student engagement, conceptual understanding, and critical thinking skills. Therefore, the PBL model can be recommended as a relevant and effective learning innovation for improving both the process and outcomes of learning in elementary school settings.